DSS1 interacts with and stimulates RAD52 to promote the repair of DSBs. Issue 2 (4th December 2019) - Stefanovie, Barbora; Hengel, Sarah R; Mlcouskova, Jarmila; Prochazkova, Jana; Spirek, Mario; Nikulenkov, Fedor; Nemecek, Daniel; Koch, Brandon G; Bain, Fletcher E; Yu, Liping; Spies, Maria; Krejci, Lumir
Abstract: The proper repair of deleterious DNA lesions such as double strand breaks prevents genomic instability and carcinogenesis. In yeast, the Rad52 protein mediates DSB repair via homologous recombination. In mammalian cells, despite the presence of the RAD52 protein, the tumour suppressor protein BRCA2 acts as the predominant mediator during homologous recombination. For decades, it has been believed that the RAD52 protein played only a back-up role in the repair of DSBs performing an error-prone single strand annealing (SSA). Recent studies have identified several new functions of the RAD52 protein and have drawn attention to its important role in genome maintenance. Here, we show that RAD52 activities are enhanced by interacting with a small and highly acidic protein called DSS1. Binding of DSS1 to RAD52 changes the RAD52 oligomeric conformation, modulates its DNA binding properties, stimulates SSA activity and promotes strand invasion. Our work introduces for the first time RAD52 as another interacting partner of DSS1 and shows that both proteins are important players in the SSA and BIR pathways of DSB repair.